Pendampingan Pembuatan Desain Kemasan Pada UMKM Di Desa Sumbernangka - Miftahol Arifin; Edy Purwanto; M. Munir Syam AR (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Sumbernangka is one of the villages in Arjasa District which has various potentials that need to be developed. This service activity is very important to carry out immediately in order to create independent and prosperous MSMEs. There are two priority problems that will be resolved through this service activity, namely the problem of MSME actors not being aware of the importance of packaging design and the problem of not knowing how to create attractive packaging designs. Therefore, this activity was carried out with the aim of providing education to the public about the importance of packaging design and providing training on how to make good packaging. The activities carried out are in the form of outreach and training. This method is deemed appropriate to solve the problems experienced by SMEs in Sumbernangka Village. There are three stages carried out during the implementation of activities, namely the activity preparation stage, activity implementation stage and activity evaluation stage. The socialization and training activities carried out were able to increase participants' understanding of packaging design. Apart from that, this activity is also able to increase the competency of MSMEs in Sumbernangka village in creating packaging designs using the Canva application.